2015
DOI: 10.5194/hess-19-3807-2015
|View full text |Cite
|
Sign up to set email alerts
|

Influence of solar forcing, climate variability and modes of low-frequency atmospheric variability on summer floods in Switzerland

Abstract: Abstract. The higher frequency of severe flood events in Switzerland in recent decades has given fresh impetus to the study of flood patterns and their possible forcing mechanisms, particularly in mountain environments. This paper presents a new index of summer flood damage that considers severe and catastrophic summer floods in Switzerland between 1800 and 2009, and explores the influence of external forcings on flood frequencies. In addition, links between floods and low-frequency atmospheric variability pat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 65 publications
(103 reference statements)
2
12
0
Order By: Relevance
“…2,3,4,5,6). Further empirical associations between flood frequency and solar activity in records from the Alpine region and central Spain (Moreno et al, 2008;Peña et al, 2015;Vaquero, 2004;Wirth et al, 2013) as well as the agreement with a flood reconstruction from multiple large European rivers of the last 500 years (Glaser et al, 2010) suggest a larger spatial relevance (central Europe) of the flood signal from the Ammer catchment.…”
Section: Mechanism For a Solar Influence On Flood Frequencymentioning
confidence: 64%
“…2,3,4,5,6). Further empirical associations between flood frequency and solar activity in records from the Alpine region and central Spain (Moreno et al, 2008;Peña et al, 2015;Vaquero, 2004;Wirth et al, 2013) as well as the agreement with a flood reconstruction from multiple large European rivers of the last 500 years (Glaser et al, 2010) suggest a larger spatial relevance (central Europe) of the flood signal from the Ammer catchment.…”
Section: Mechanism For a Solar Influence On Flood Frequencymentioning
confidence: 64%
“…However, Wilson et al (2010) found that there is a clear tendency for early occurrence of spring floods which is likely due to an earlier snowmelt due to a rise in temperature. The declining trend in the frequency of summer rain-on-snow flood events in Northern and Eastern Europe found in our study can also be likely due to earlier snowmelt, which reduces the number of snow related events in the hydrological summer In the Alps, Schmocker-Fackel and Naef (2010) and Peña et al (2015) found that the frequency of summer flooding in Switzerland has been on the rise in the last four decades and associated the changes to patterns of low-frequency atmospheric variability and corresponding changes in the frequency of heavy precipitation. Similar results are presented by Pekárová et al, (2016) who identified increasing frequency of large floods along the Danube river.…”
mentioning
confidence: 86%
“…In the north of the Alps, a similar weather situation associated with heavy rainfall that lasts for several days, which triggers most of the summer flooding in central Europe defines the flood regime (Böhm and Wetzel, 5 2006). A similar mechanism leads to flooding in the higher mountain ranges, but it can be accompanied by glacier and snowmelt, which enhance the antecedent catchment wetness (Merz and Blöschl, 2003;Parajka et al, 2010, Peña et al 2015.…”
Section: Discussionmentioning
confidence: 99%
“…Interannual to multidecadal variability of heavy precipitation and flood events in the Alpine region are also related to large-scale atmospheric teleconnection patterns. Peña et al (2015) emphasized the role of the Summer North Atlantic Oscillation (SNAO) in generating flood variability in Swiss rivers. The east Atlantic (EA) pattern and SNAO modify the frequency of atmospheric circulation patterns controlling debris flow occurrences in the Swiss Alps (Toreti et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the variability and predictability of flood occurrences have been addressed in many research studies (e.g., Jacobeit et al, 2003;Czymzik et al, 2010;Peña et al, 2015;Schillereff et al, 2014;Ionita et al, 2008Ionita et al, , 2015.…”
Section: Introductionmentioning
confidence: 99%